2019
DOI: 10.1093/iob/obz015
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphology of Neotropical Electric Fishes: An Integrative Approach to Testing the Relationships between Form, Function, and Trophic Ecology

Abstract: Synopsis The relationship between form and function is thought to play an integral role in structuring broad-scale patterns of morphological evolution and resource utilization. In ecomorphological studies, mechanical performance is widely understood to constrain the evolution of form and function. However, the relationship between form, function, and resource utilization is less clear. Additionally, seasonal fluctuations in resource availability may further complicate patterns of resource use. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…This trend is consistent with the adaptive value of these traits with respect to feeding kinematics. Indeed, the trend in functionally relevant components of anatomical structures exhibiting fast rates and high evolvability has been noted in other teleosts groups (i.e., Electric fishes [52,53], cichlids, pomacentrids, centrarchids, and labrids [54]), and may reflect a general trend across organisms [55,56]. In terms of disparity, it is notable that the tooth-plate module exhibited the highest levels for both the mandible and lower pharyngeal jaw.…”
Section: Evolvability Of the Feeding Apparatus Is Consistent Across Hmentioning
confidence: 82%
“…This trend is consistent with the adaptive value of these traits with respect to feeding kinematics. Indeed, the trend in functionally relevant components of anatomical structures exhibiting fast rates and high evolvability has been noted in other teleosts groups (i.e., Electric fishes [52,53], cichlids, pomacentrids, centrarchids, and labrids [54]), and may reflect a general trend across organisms [55,56]. In terms of disparity, it is notable that the tooth-plate module exhibited the highest levels for both the mandible and lower pharyngeal jaw.…”
Section: Evolvability Of the Feeding Apparatus Is Consistent Across Hmentioning
confidence: 82%
“…Predators generally had longer jaws than fishes feeding at a lower TP and, although gape size is not directly related to jaw length, the positive association was consistent with predictions of TP increasing with gape size (Arim et al., 2007). Longer jaws can increase gape‐distance for prey capture, increase mouth closing speeds, or increase suction feeding velocities in predators (Hulsey & Garcia de Leon, 2005), while shorter jaws maximize bite force needed to feed on hard‐bodied prey items (Ferry et al., 2015; Westneat, 2004; Evans et al, 2019). The shape of the nonlinear association showed that top predators rarely had small jaw sizes, while species with extremely long jaws were not commonly omnivorous, herbivorous or detritivorous.…”
Section: Discussionmentioning
confidence: 99%
“…For evaluating the phylogenetic independence of morphological characters, we tested for the “phylogenetic signal” of trait values among species. For this, we constructed a phylogenetic tree using the maximum likelihood (ML) method based on the cytochrome oxidase‐I (COX‐I) sequences of the species (Blomberg et al, 2003; Evans et al, 2019). The best ML tree using DNA substitution models (Arenas, 2015) was inferred based on Akaike's Information Criterion (AIC) values after which Abouheif's C‐ mean test for serial independence was employed (Abouheif, 1999).…”
Section: Methodsmentioning
confidence: 99%